PENGGUNAAN MARKETPLACE SHOPEE TERHADAP VOLUME PENJUALAN DI WIDYA STORE BANDUNG - Sukma, Roby; Franciskus Antonius Alijoyo (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
The marketplace is currently very loved by the community because using the marketplace facilitates the transaction process and with the marketplace people can choose the desired product or service directly from home. Therefore, with the high public interest in using this marketplace, Widya Store began to change its sales system to a marketplace to increase its sales volume. This study aims to find out how the influence of this Marketplace can have a very significant impact on sales volume and find out how to attract customers to the products sold on the Shopee Marketplace. The research method used is qualitative research using observation, interviews and literature studies. The results of this study found that the use ofthis marketplace is proven to be able to drive sales volume at Widya Stores by 35% inearly 2023.